2018
DOI: 10.3892/ol.2018.8246
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between TNF-α-308 gene polymorphism and susceptibility to cervical cancer

Abstract: Tumor necrosis factor-α (TNF-α) is closely related to the occurrence of human cancers. Cervical cancer seriously affects female health. Therefore, our study aimed to investigate the correlation between the polymorphism of TNF-α-308 gene and susceptibility to cervical cancer. Whole blood was collected from 142 patients with cervical cancer and 150 healthy controls. PCR-RFLP was used to detect the polymorphism of TNF-α-308 and the correlation between polymorphism of TNF-α-308 and the susceptibility to cervical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(21 reference statements)
0
9
0
2
Order By: Relevance
“…SNPs are the substitution of a single base pair for another and play a key role in the evaluation of disease susceptibility, drug efficacy, and adverse drug reactions 118 . Some investigators have analyzed the TNF‐α G>A rs1800629 SNP 119‐121 . According to Duarte et al, 119 the TNF‐α GA genotype showed a modest but statistically significant difference in genotype distribution (16.4% in controls vs 25.6% in patients with cervical cancer; n = 439; P = .012).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs are the substitution of a single base pair for another and play a key role in the evaluation of disease susceptibility, drug efficacy, and adverse drug reactions 118 . Some investigators have analyzed the TNF‐α G>A rs1800629 SNP 119‐121 . According to Duarte et al, 119 the TNF‐α GA genotype showed a modest but statistically significant difference in genotype distribution (16.4% in controls vs 25.6% in patients with cervical cancer; n = 439; P = .012).…”
Section: Discussionmentioning
confidence: 99%
“…Al igual que nuestros resultados, no encontraron diferencias significativas en las frecuencias genotípicas y alélicas entre el grupo de pacientes con cáncer de cuello uterino y el grupo control; sin embargo, observaron que el genotipo A/A pudiera estar asociado con el incremento del riesgo de desarrollar cáncer de cuello uterino en 1,46 veces, con un intervalo de confianza del 95% de 0,32 a 6,67. Además, encontraron que pacientes con el alelo A tuvieron cáncer cervical de alto grado de malignidad (32).…”
Section: Discussionunclassified
“…Li y col. (32), también correlacionaron 5 polimorfismos en la región promotora del gen TNFα (rs361525, rs1800629, rs1800750, rs1799964, and rs673) con la susceptibilidad a desarrollar cáncer de cuello uterino, en 946 muestras de sangre periférica de mujeres de la etnia Han de la provincia de Shandong, de las cuales 452 fueron diagnosticadas con carcinoma cervical de células escamosas y 492 pacientes controles. Las muestras fueron analizadas empleando PCR SNP`s utilizando el método de la sonda TaqMan.…”
Section: Discussionunclassified
“…TNF-α is a well-established driver of inflammation that may promote the growth and progression of cancer [27]. The two most commonly studied SNPs are in the promoter region of TNF , two G versus A transitions at positions −238 and −308; these have been shown to influence the expression of TNF-α [28,29]. A large number of studies have investigated the associations of TNF -238 G/A and/or −308G/A variants with cervical cancer risk, but results are contradictory [30,31].…”
Section: Discussionmentioning
confidence: 99%